THE EFFECT OF OWNERSHIP STRUCTURES AND FINANCIAL FIRM PERFORMANCE TOWARD EXECUTIVE COMPENSATION (EMPIRICAL STUDY ON CONSUMER CYCLICALS SECTOR COMPANIES LISTED IN INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019) - Kamtono, Livia (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
This study aims to determine the effect of ownership structures and company